Synthesis and characterization of alcohol-free tyrosinase encapsulated silica aerogel - Sani, Nor Suriani (2009)
Encapsulation of tyrosinase enzyme into nanoporous silica aerogel via an alcohol-free colloidal sol-gel route using rice husk ash (RHA) as silica source was studied. Tyrosinase encapsulated silica aerogel (TESA) was synthesized with and without solvent extraction process at room temperature and neutral pH in order to study their effect on the enzyme activity and to minimize enzyme denaturation. The physicochemical properties of TESA was characterized by X-ray diffraction (XRD) technique, fourier transformed-infrared (FTIR) spectroscopy, field emission-scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) analysis, transmission electron microscopy (TEM) and thermogravimetric analysis (TGA). These characterizations confirmed tyrosinase in TESA was located inside the network of silica aerogel. Enzymatic activity of tyrosinase was assayed through the reduction of ascorbic acid using UV Visible spectrophotometer. Almost 98% of tyrosinase was successfully loaded into silica aerogel as determined by the leaching test of TESA. TESA without solvent extraction showed higher tyrosinase activity than TESA extracted by amyl acetate/acetone (v/v:1/1). The highest activities for both TESA were obtained with 10.00 mg/mL of enzyme loading that was aged for 2 days. The stability of tyrosinase in TESA was enhanced towards extreme temperature as well as acidic and basic conditions. Free tyrosinase was totally inactivated at pH < 4 and pH > 9 and at temperature exceeding 55 °C, while TESA showed a significant activity at these conditions. In the application of TESA, about 80% of phenol was removed after 3 hours contact with TESA. The reusability of tyrosinase in TESA was observed to be very high since TESA can be reused to remove phenol up to 10 times without significant loss. As a conclusion, nanoporous silica aerogel from RHA prepared with and without solvent extraction techniques can be used as suitable support for the improvement of the tyrosinase stability and it can be applied to remove phenol.